AN ANALYSIS OF THE PHONOLOGICAL AND LEXICAL CHANGES FROM TIGAWASA DIALECT TO DENCARIK DIALECT: A DESCRIPTIVE STUDY - ., I Komang Bramawan; ., Dr. I Gede Budasi, M.Ed.; ., G.A.P. Suprianti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk menjelaskan perubahan fonologis dan leksikal dialek Tigawasa ke Dencarik. Penelitian deskriptif kualitatif ini menggunakan 3 informan dari masing masing dialek, yang dibagi atas satu orang ditunjuk sebagai informan utama, sedangkan 2 orang ditunjuk sebagai informan pendamping Data diperoleh dengan mengunakan 4 teknik, yaitu: peneliti, observasi, rekaman, dan daftar kata Swadesh dan Nothofer. Dialek di desa Tigawasa dan Dencarik unik karena situasi dan kondisi desa tersebut. Hasil menunjukkan bahwa 4 kata apocope, 4 kata syncope, 10 suku kata (haplology), 3 kata epenthesis, 3 kata prothesis, 3 kata paragoge, dan 48 kata termasuk kategori perubahan bunyi abnormal. Perubahan leksikal yang terdapat dari dialek Tigawasa ke dialek Dencarik dapat dikategorikan sebagai berikut: 10 kata termasuk penyalinan leksikal, 10 kata termasuk kata yang sudah punah, 4 kata yang di kompres, dan 4 kata yang dicampur.Kata Kunci : dialek, perubahan fonologi, perubahan leksikal This study aimed at describing the phonological and lexical changes from Tigawasa to Dencarik dialect. This research was a descriptive qualitative research. In this study, there were three informants selected for each dialect, One person was appointed as the main informant, where as two others were appointed as the secondary informants. The obtained data were collected by using these techniques, namely: the researcher, observation, recording, and Swadesh’s and Nothofer’s wordlist. The results of the data analysis show that there were four words which were categorized as deletion in the final word position (apocope), four words as deletion in the middle word position (syncope), ten words were as deletion of syllable in the word (haplology), three words as addition in the middle word position (epenthesis), three words were as addition in the initial word position (prothesis), three words were as addition in the final word position (paragoge), forty eight words as abnormal sound change. The lexical changes which occur from Tigawasa dialect to Dencarik dialect were categorized as follows: ten words were categorized as lexical copying, ten words were as lost words, four words were as compressions (initials) and four words were as blends.keyword : dialect, phonological changes, lexical changes